Experiences and perceptions of clinical research participation at an academic medical center - Joshua T. CLARK; Angela BURRELL; Amber ARNOLD; Travis W. SCHMITZ; Lei ZHANG; Daniel W. JONES; Richard L. SUMMERS; Whitney BONDURANT; Vinayak K. NAHAR (Journal of Health and Social Sciences)
Introduction: The purpose of this study was to capture experiences and explore perceptions of clinical faculty research participation at an academic medical center in the southeastern United States to allow leadership to train, recruit, and retain faculty members and increase research production by better understanding motivations for and barriers to academic research participation. A secondary objective was to gauge the impact of coronavirus disease 2019 (COVID-19) on clinical faculty and their research experiences. Methods: This explanatory sequential mixed methods study was conducted in two phases. In Phase I, a quantitative questionnaire was distributed to 482 individuals across 18 of the academic medical center’s 23 School of Medicine departments. Data were analyzed to determine if research experiences differed based on research participation, gender, tenure status, early career investigator status, and faculty rank. In Phase II, qualitative in-person interviews were conducted using a semi-structured interview guide. Results: In total, 100 Phase I questionnaires were completed, 93 of which met study inclusion criteria. Sixteen Phase I participants opted-in to Phase II interviews, and 11 interviews were successfully completed. Results from Phases I and II indicated several important emerging themes, leading to the creation of three overarching study categories: barriers to clinical research, divide in research training and education, and the impact of COVID-19. Discussion: Results indicated several important emerging themes related to clinical research experiences and perceptions at an academic medical center. These findings will provide leadership with important insight into the experiences and perceptions of clinical faculty and their research participation at the academic medical center, including their motivations for and barriers to research participation.